ENERGY TECHNOLOGY OF DAIRY PRODUCTS QUALITY ASSESSMENT USING IMPEDANCEMETRY - Sorokin, M.; Huzenko, V.; Vasylenko, D. (Municipal economy of cities. Series: «Economy science», 2024)
The article examines the peculiarities of milk quality research using the impedance method. Impedance is a complex parameter that characterises the interaction of the electric current with milk. The authors have developed a methodology based on the specified method to assess the quality of dairy products and have created a hardware and software complex that makes it possible to analyse the quality of dairy products. The research, conducted using the developed hardware and software complex, revealed several regularities characterising different types of milk. These regularities demonstrate the relationship between the impedance signal and the milk fat index. Analysis of the obtained data allowed us to identify differences in impedance between samples with varying fat content and origin from different manufacturers. The developed experimental setup prototype enabled the following research stages: checking the change in voltage during the passage of an alternating electric current through milk. This work used the AFS Sensor DAQ data acquisition system, designed for sensor control projects and which runs with NI LabVIEW software, for data output. The authors tested the installation while investigating the impedance of dairy products with different fat content and from multiple manufacturers. During the experiment, we measured the impedance and capacitance of the samples, and the obtained data became available on a PC for further analysis. The aim was to study the electrical properties of dairy products and their dependence on the composition and manufacturer. The obtained results represent valuable information for dairy product production and quality control. It is possible to use them to optimise production processes, ensure stable product quality, and improve consumer characteristics of dairy products. The obtained data contribute to a deeper understanding of the relationship between the impedance signal and the composition of dairy products, which can lead to the development of new methods of analysis and evaluation of the quality of food products. In addition, these studies have implications for food science and nutrition.